Identifying Dental and Oral Health Problems of Kindergarteners using KAFOGI Dental Photography - Dwitama, Muhammad Bima Rizki; Faiga, Nilna Naila; Salim, Nabilah; Wijaya, Monika Amaria Putri; Mahardika, Grahania Octaviono; Basiroh, Eris; Hidayatillah, Pratiwi Nuzulil; Laksono, Amanda Brigitta; Nosla, Nadiah Salsabila; Mensana, Mario Powa; Hanani, Atika; Setijanto, R. Darmawan (Faculty of Dental Medicine Universitas Airlangga, 2020)
Background: Caries is one of the most common dental and oral health problems in preschool students. An epidemiological study reported that students of a kindergarten under Mojo Public Health Center coverage have a high caries index (def 6.9). The parental role, especially maternal role, significantly affects the child's dental and oral health. Children will also learn from the attitudes and behavior of their parents and close relatives. The preliminary epidemiological study also found that 72.7% of the mothers had higher knowledge levels, and 27.3% of the mothers had lower knowledge levels.The many behavioral theories that state that knowledge is one of the factors that influence a person in behavior. In the era of globalization, information dissemination is done quickly and easily with the help of several media. Purpose: An empowerment program was conducted to increase participants' knowledge levels using Dental Photo Card (KAFOGI). Method: This descriptive research involving 73 mothers from kindergarten. They were given pre-test before doing the programs. After viewing dental health education video, the mother were tested to place the image or photograph of teeth and placed to the right place in KAFOGI card. Results: As much as 78.1% of respondents have answered correctly, while respondents who answered incorrectly were 21.9%. Conclusion: With your knowledge of the number of child caries teeth, you will behave in accessing information about the child's oral health.